As administrações petistas em Diadema (1983-1996): entre o poder político e as demandas sociais - Santos, Joana Darc Virgínia dos (2014)
This research aims to analyze the acting of the Partido dos Trabalhadores (Workers Party) in face of the social demands in Diadema from 1983 to 1996, highlighting the struggles for housing. A city that has been marked by illegality housing, lack of infrastructure, high rates of violence, and low rates of human development, resulting by economic policies and privileging of industrial interests adopted in a local and national level, Diadema City has experienced shortages of basic infrastructure, the worst rates of human development of the State and intensive conflicts between social activists and landowners. With the achievement of the first PT city council in Brazil which lasted for three consecutive administrations from 1983 to 1996, thousands of workers who lived in Diadema yearned for the reform of the State with its apparatus for directing the popular demands. From the immanent analysis of meetings minutes of Diretório de Diadema; testimonies, newspaper items and documents produced by PT militants, government and non-governmental organizations on the performance of PT from 1983 to 1996, it was possible to find that although there had been a reversal of priorities in the budget allocation of the local government during the PT administrations in the city, it was consolidated the increasing alienation of the PT in relation to social struggles and adoption of graft in their strategies. It was evident that by adopting the graft strategy, the PT in Diadema increasingly incorporated neoliberal practices and began to assume an important role in the new period of Productive Restructuring in Brazil: inauthentic building consents, which expanded the precariousness of work, accommodation conflicts of capital and the development of industrial project, leveraging business in the city